Penerapan Strategi Make A Match Untuk MeningkatkanKemampuan Memahami Materi IPS Pada SiswaKelas X PMS B SMK Negeri 3 SukoharjoTahun Ajaran 2015/2016 - Novitasari, Eriska; , Prof. Dr. Harsono, SU (2016)
This study aims to improve the comprehend ability of the IPS material by applying make a match strategy. This research is a classroom action research which conducted in three cycles and every cylces have four phase, namely: (1) planning; (2) implementation; (3) observation; (4) Reflection.The subject of this research are 36 students of X PMS B class of SMK N 3 Sukoharjo. To collecting the data the researcher use observation, field notes, documentation, and testing method.In analyzing the data the researcher use comparative descriptive and critical analysis techniques.The results of this study show that there are improvement of comprehend ability of the material IPS economy that can be seen by the indicators, there are: 1) the ability to mention before actions 19.44% and at the end of the action becomes 72.2%, 2) the ability to explain before the action 13.9% and in the final action 58.3%, 3) giving the example before the action 25% and at the end of the action 75%, 4) the ability to conclude before the action 13.89% and at the end of the action 66.7%. The results showed an increased ability to understand the material IPS based on the value of daily tests from 25% increased to 97%. Students who obtain more value from Criterion Complete Minimal (KKM) is the first cycle were 19 students or 53%, the second cycle increased by 26 students, or 72%, and the third cycle increased by 35 students or 97%. Based on this research can be concluded that the use of strategies make a match can improve the ability to understand the IPS material in class X PMS B SMK Negeri 3 Sukoharjo.